The Effect of Chromebook Utilization on Improving Digital Literacy and Creativity of SMP Negeri 2 Tabang Students - Jayan Trianus; Nuril Huda; Victor Maruli Tua L. Tobing (FKIP - Universitas Riau, 2026)
The study aims to analyze the influence of Chromebook use on improving digital literacy and creativity of students at SMP Negeri 2 Tabang. The research is based on the gap between the adoption of technology in education and the development of digital competencies, such as digital literacy and creativity, which are still challenges. The research method uses a descriptive qualitative approach with data collection techniques through observation, student interviews, and documentation for one month. The research subjects amounted to 20 students in class 9B who were selected using convenience sampling techniques. Research shows Chromebooks realize operational digital literacy, where 18 out of 20 students can operate devices independently, and visual creativity using templates and design features. However, the research reveals the limitations of digital literacy development, such as the ability to evaluate the credibility of information sources, and transformative creativity to generate original ideas. Technology integration needs to be accompanied by a pedagogical approach specifically designed to develop critical thinking skills and deep creativity.